Unveiling of Stishovite and Coesite in the Prismatine-Bearing Granulite from Waldheim, Germany: A Potential Role of Supercritical Fluids of Ultrahigh-Pressure Origin - Thomas, Rainer; Davidson, Paul; Rericha, Adolf; Recknagel, Ulrich (Geography, Earth Science and Environment: Research Highlights Vol. 6, 2025)
Stishovite, the tetragonal high-pressure polymorph of SiO2, was named by the Russian high-pressure physicist Sergey M. Stishov, who, together with Popova, first synthesized the mineral in 1961. This mineral is very rare at the Earth's surface, having only been found in known or suspected meteorite craters. For the first time in the sixty years since the synthesis of stishovite, unambiguous evidence of stishovite formed in the deep Earth has been reported. A minimum pressure of about 7.5 GPa at 1000 °C is necessary for the formation of stishovite, corresponding to a depth of about 230 km. The study reports the identification of stishovite and coesite as inclusions in mineral grains from the Waldheim granulite. This implies that the stishovite was transported upwards, probably very rapidly, to a depth of about 130 km, corresponding to the highest pressure indicated by newly identified coesite in the prismatine of the Waldheim granulite, and continuing up to the depth of emplacement of the Waldheim prismatine granulite. The analysis of the Raman spectra obtained from a metastable trapped stishovite micro-crystal shows that all the diagnostic Raman bands are present. However, given the metastability of the stishovite at room temperatures and pressures, this mineral breaks down step-by-step into stable polymorphs, first coesite and then quartz and cristobalite, during the Raman stimulation. The rare coesite crystals in prismatine have also resulted from the irreversible transformation from stishovite. Although the Waldheim occurrence may be unique, it can be suggested that Raman analysis of co-trapped crystals in similar deep-seated rocks, an area of limited previous research, may prove an essential innovation in the study of mantle processes. While the host rocks indicate no more than granulite facies temperatures and pressures, their minerals may contain co-trapped crystals from a much deeper source with higher temperatures and pressures.